Temporal Fossa Atrophy in Aesthetic Medicine: Anatomy, Classification, and Treatment. Issue 10 (October 2020) - Idone, Francesco; Bolletta, Elisa; Piedimonte, Andrea; Paternostro, Ferdinando
Abstract : Summary: Hyaluronic acid fillers indisputably represent an important tool for face rejuvenation and volume restoration. The temporal area has recently been considered as a potential site of injection. As it happens in the middle face and in other regions of the face, the temporal fossa changes according to the aging process. In a young person, the temple profile has a fullness aspect, and this contributes to giving the face a beautiful and healthy appearance. With age, the loss of volume leads the bone prominences to be visible. The aim of this article is to classify the temporal fossa atrophy and get better into the anatomy, identifying the ideal plane to inject in, through the use of a safe and reliable technique. Cadaver dissections have been performed to specifically describe the anatomy of the temple layer by layer. The authors' preferred technique, called interfascial by cannula implantation, is discussed. All the treated patients reported a good improvement by survey according to the Global Aesthetic Improvement Scale scale. No major complications were detected. No ecchymosis neither swelling were documented. Although further studies are necessary to broaden the casuistry and better verify the potentiality of this technique, the authors do believe that it could be considered a very reliable procedure with pretty consistent results, if supported by an adequate and imperative anatomical knowledge.